MELAWAN PENGANGURAN: PEMIKIRAN EKONOMI AL-SHAYBANI - HIKAM, MUHAMMAD (At-Taradhi Jurnal Studi Ekonomi, 2015)
Abstract: This paper seeks to show that government policies that restrict intervention or no intervention at all in the unemployment rate become a-historical view and even irrational. The Postulat is in historical data that occurs at the time of al-Amin and al-Ma'mun and "initiation al-Shayban?" -if not be called "theory of al-Shayban?". In line with the context of the economic crisis at the time of al-Amin, the initiation of al-Shaybani which isimplemented by al-Ma'mun may be referred to unemployment"stabilization policy". The idea of al-Shaybani on social security establishedthe coherence with contractual policy which is substantively has six features: (1) share work and early retirement. (2) A policy in favor of the cost of labor turnover. (3) Pro?t sharing. (4) Low wages subsidy and a reduction in payroll taxes. (5) Subsidy ofrecruitment of new workers. (6) The transfer of pro?ts. This contractual policy is voiced by Lindbeck and Snower (1988), M. Weitzman (1984).